Aging well together - A mini-review - Rohr, Margund; Lang, Frieder (Gerontology, 2009)
We review the contribution of social integration on the process of successful aging. Building on empirical findings, we describe three major challenges and potentials of social contexts that are related to the elasticity, role differentiation, and the risk potentials of social relationships in adulthood. We propose a model of aging well together that advances concepts of selection, optimization, and compensation to social aging and to the mastery of relationship demands. According to the model, individuals are choosing and seeking positive social experience, improving the fit of their social environment, and they counterbalance the risks of social contact. We provide exemplary empirical evidence for the existence of such regulatory contributions of social bonding on aging well. Several implications for researchers as well as practitioners in the field of gerontology are extracted. Future research needs to further disentangle the dynamic and complex nature of social relationship effects on positive aging. © 2009 S. Karger AG, Basel.